(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
The results of studying copper concentrations in arable and meadow soils in diﬀerent areas of Gomel region are analyzed in the article. This research was carried out with an interval of four years. The ﬂuctuations of weighted average values of copper in arable and meadow soils were in the range of 1.44–2.16 and 1.55–2.20mg/kg in 2013, and, respectively, 1.42–2.17 and 1.83–2.20mg/kg in 2017. The areas with increased concentrations of copper in soils are expanding over time. In 2013, speciﬁc concentrations of copper above 1.51mg/kg were found in 47.9% of examined arable soils and 54.2% of grassland soils. In 2017, the areas increased to 50.2 and 60.9%, respectively.